PLANTING PATTERNS ON RAINFALL PAID LAND FOR INCREASING IP 100 TO IP200 IN POSO REGENCY, CENTRAL SULAWESI - Suwitra, I Ketut; Ardjanhar, Asni; Fattah, Abdul; Supriadi, Khojin; Udiarto, Bagus K; Khasanah, Nur; Negara, Abdi; Mustakim, Mustakim (Universitas Tadulako, 2025)
Determination of cropping patterns in rainfed paddy fields is very necessary so that crop failure can be avoided and to maximize profits for farmers. The study aimed to obtain cropping patterns in rainfed lowland areas that can produce high yields and increase farmer incomes. The research was carried out in Tonusu Village, Pamona Puselemba District, Poso Regency, Central Sulawesi Province. The research was conducted from January 2018 to December 2018, the research consisted of cropping patterns and variety rotation during two growing seasons, namely the rainy season (MH) and the dry season (MK). Planting pattern of paddy farmers - bero (IP.100) and rice cropping pattern - paddy (IP.200. Introduction pattern). The results showed that: Farming analysis of IP 100 and IP 200 Tonusu Village, Pamona Puselemba District, Poso Regency scale per hectare At MT. I and MT. II can provide a profit of Rp. 15,130,000, - with an R/C: Ratio of 3.01 to farmers (IP 200) per MT. The value of farming on the farmer's pattern (IP 100) provides a profit of IDR 10,170,000 with an R/C: Ratio of 1.77.